Spinal bromodomain-containing protein 4 contributes to neuropathic pain induced by HIV glycoprotein 120 with morphine in rats. Issue 6 (11th April 2018) - Takahashi, Keiya; Yi, Hyun; Liu, Ching-Hang; Liu, Shue; Kashiwagi, Yuta; Patin, Dennis J.; Hao, Shuanglin
Abstract : The symptoms of HIV-sensory neuropathy are dominated by neuropathic pain. Recent data show that repeated use of opiates enhances the chronic pain states in HIV patients. Limited attention has so far been devoted to exploring the exact pathogenesis of HIV painful disorder and opiate abuse in vivo, for which there is no effective treatment. Bromodomain-containing protein 4 (Brd4) is a member of the bromodomain and extraterminal domain protein (BET) family and functions as a chromatin 'reader' that binds acetylated lysines in histones in brain neurons to mediate the transcriptional regulation underlying learning and memory. Here, we established a neuropathic pain model of interaction of intrathecal HIV envelope glycoprotein 120 (gp120) and chronic morphine in rats. The combination of gp120 and morphine (gp120/M, for 5 days) induced persistent mechanical allodynia compared with either gp120 or morphine alone. Mechanical allodynia reached the lowest values at day 10 from gp120/M application, beginning to recover from day 21. In the model, gp120/M induced overexpression of Brd4 mRNA and protein at day 10 using RT-qPCR and western blots, respectively. Immunohistochemical studies showed that Brd4 at day 10 was expressed in the neurons of spinal cord dorsal horn. BET inhibitor I-BET762 dose-dependently increased the mechanical threshold in the gp120/M pain state. The present study provides preclinical evidence for treating HIV neuropathic pain with opioids using the BET inhibitor.